Synthesis and characterization of new hybrid microspheres with amide functionalization - Beata Podkościelna; Karolina Fila; Małgorzata Gil; Janina Nowak (Adsorption Science & Technology, 2017)
In this article, synthesis and characterization of new crosslinked hybrid microspheres are presented. This material was obtained by the emulsion-suspension polymerization of 1,4-divinylbenzene and trimethoxyvinylsilane. In the case of introducing biologically active functional groups on the surface of microspheres, methacrylamide as a third monomer was added. Chemical structures of all new materials were confirmed by the spectroscopic method (attenuated total reflectance-Fourier transform infrared spectroscopy) and elemental analysis. The influence of comonomer structure on the physico-chemical properties of the hybrid microspheres was investigated. Porous structures in a dry state were studied by means of nitrogen adsorption–desorption measurements. Thermal stabilities and degradation behavior of the obtained copolymers were characterized by the use of thermogravimetric/derivative thermo-gravimetric analysis.